Crystallization and initial crystallographic analysis of covalent DNA‐cleavage complexes of Staphyloccocus aureus DNA gyrase with QPT‐1, moxifloxacin and etoposide. Issue 10 (1st October 2015) - Srikannathasan, Velupillai; Wohlkonig, Alexandre; Shillings, Anthony; Singh, Onkar; Chan, Pan F.; Huang, Jianzhong; Gwynn, Michael N.; Fosberry, Andrew P.; Homes, Paul; Hibbs, Martin; Theobald, Andrew J.; Spitzfaden, Claus; et al.
<x xml:space="preserve">Abstract</x> Fluoroquinolone drugs such as moxifloxacin kill bacteria by stabilizing the normally transient double‐stranded DNA breaks created by bacterial type IIA topoisomerases. Previous crystal structures of Staphylococcus aureus DNA gyrase with asymmetric DNAs have had static disorder (with the DNA duplex observed in two orientations related by the pseudo‐twofold axis of the complex). Here, 20‐base‐pair DNA homoduplexes were used to obtain crystals of covalent DNA‐cleavage complexes of S. aureus DNA gyrase. Crystals with QPT‐1, moxifloxacin or etoposide diffracted to between 2.45 and 3.15 Å resolution. A G/T mismatch introduced at the ends of the DNA duplexes facilitated the crystallization of slightly asymmetric complexes of the inherently flexible DNA‐cleavage complexes.